2005
DOI: 10.1007/s00068-005-1443-z
|View full text |Cite
|
Sign up to set email alerts
|

Simulated Osteopenia Impairs Metaphyseal Bone Ingrowth of Metal Implants in an Animal Model

Abstract: European Journal of TraumaAb stract Background and Purpose: Cementless total joint replacement in osteopenic bone is suspected to deteriorate long-term survival of implants because results in dental implantology research indicate that bone ingrowth of dental implants in osteoporotic bone is impaired. The present investigation was designed to determine whether osteopenic bone stock, experimentally created in ovariectomized rats, influences the active bone-implant integration process. Material and Methods: 40 Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The implants were inserted mainly into the rat tibia (65.85%) or in the femur (19.5%). In 1 study, implants were placed into the medullary canal of the femur, in 3 studies, they were placed into healed post‐extraction sockets and in 1 into the maxillary arch …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The implants were inserted mainly into the rat tibia (65.85%) or in the femur (19.5%). In 1 study, implants were placed into the medullary canal of the femur, in 3 studies, they were placed into healed post‐extraction sockets and in 1 into the maxillary arch …”
Section: Resultsmentioning
confidence: 99%
“…32 The implants were inserted mainly into the rat tibia (65.85%) or in the femur (19.5%). In 1 study, implants were placed into the medullary canal of the femur, 33 in 3 studies, they were placed into healed post-extraction sockets 29,34,35 and in 1 into the maxillary arch. 36 Rabbits were used in 10 studies (17.54%) and in 60% of these studies, the age of the animals was between 4 and 12 months.…”
Section: Animal Modelsmentioning
confidence: 99%
“…It was noted that implants immersed with bisphosphonates were synthesised using titanium alloys and coated with hydroxyapatite before immersion. However, the effect of hydroxyapatite coating was reported to deteriorate bone-implant ingrowth in osteoporotic patients [32,33]. Although they reported that there are undesired effects of hydroxyapatite, their study groups were coated before immersion.…”
Section: Discussionmentioning
confidence: 99%
“…Gao et al [32] stated that the benefit of bisphosphonate immersion on the implant surface is that they impact osteoclasts by eradicating their proliferation activity, which is desirable for patients with osteoporosis. Another study suggested that the use of hydroxyapatite-coated implants enhances bone mineralisation, formation, and mechanical stability; however, using such implants may lead to loosening and inflammation in the implant site due to the damage it causes to the bone matrix [33].…”
Section: Implant Surface Nanotopographymentioning
confidence: 99%